The Index as a New Concept towards an Integrated Framework for the Electronic Patient Record - Clercq, De E. (Methods of Information in Medicine, 2002)
Objective: To overcome some classical limitations of the POMR (Problem-Oriented Medical Record), including the management of divergent opinions between health professionals, in order to construct a common patient record across multiple disciplines in hospital settings and professional networks.Methods: Using a complex clinical case, we improved a POMR model previously used by GPs in order to translate it into a hospital setting. The enhanced model has been assessed through use in various ongoing clinical cases and through extended discussion with professional end-users (physicians, nurses, general practitioners, and social workers).Results: The Index concept (flexible structural link) is proposed as a major improvement in the construction of a POMR in a shared care environment.Conclusions: The Index introduces interesting new perspectives. Following its implementation in the Belgian pilot site in the CORINES project, further studies remain to be carried out in order to develop a cost/benefit assessment.
Keywords: Medical records; problem-oriented medical records; computerized patient records